GAME EDUKASI BERBASIS ANDROID PADA MATERI HIMPUNAN - Muhammad Aula Hijrah; Medika Risnasari; Muchamad Arif; Laili Cahyani; Nuru Aini (Universitas Muhammadiyah Ponorogo, 2020)
Educational game is a game that can encourage someone to think more actively and creatively in learning. During this time, learning Discrete Mathematics courses in the Informatics Education Study Program still uses media in the form of books, Power Point (PPT), and blackboards. That makes students less interested in learning. Therefore, an Android-based educational game was developed to be able to achieve learning goals in Discrete Mathematics courses, especially set topics. The research data used is the 2017 batch of Informatics Education students. The development model used is ADDIE with five stages, namely Analyze (Design), Design (Development), Development (development), Implementation (implementation), and Evaluation (evaluation). Test results by learning media experts reach 99%. The test results by material experts reached 82%. The results of individual, small group and large group trials reached 90%, 84% and 86% respectively. Based on the assessment, Android-based educational game media was declared feasible to be used as learning media in the Discrete Mathematics subject set material.